Cellular ceramics by gelatin gelcasting of emulsified suspensions with sunflower oil. Issue 9 (September 2015) - Sanches, M.F.; Vitorino, N.; Freitas, C.; Abrantes, J.C.C.; Frade, J.R.; Rodrigues Neto, J.B.; Hotza, D.
Abstract Highly porous cellular ceramics were prepared by a versatile method combining emulsification of sunflower oil in alumina suspension, using collagen as surfactant, stabilizer and gelcasting additive. Emulsified suspensions show shear thinning behavior at emulsification temperatures, and their rheology was related to the volume fraction of dispersed oil droplets, collagen contents and stirring rate, based on a suitable Taguchi plan. This provides guidelines for the dependence of microstructural features on these processing parameters. The robustness of the method was demonstrated by the ability to perform early stages of burnout at relatively high heating rates, without risks of collapse or onset of factures in the resulting cellular ceramics. Combined DTG/DTA/FTIR studies were used to analyse the burnout stages, and provide guidelines to minimize emissions of gases with safety or environmental risks.